An investigation of crack propagation in an insect wing using the theory of critical distances. (1st June 2020) - Schmidt, Jonas; O'Neill, Maeve; Dirks, Jan-Henning; Taylor, David
Graphical abstract: Highlights: Veins act as crack-stoppers in the wings of locusts. Finite element models of the crack at various stages propagating through a vein. Analysis using the Theory of Critical Distances (Line Method). Accurate predictions of the effect of the vein. Potential to apply the same approach to crack-resistant engineering materials. Abstract: Materials often have toughening mechanisms at different length scales. An interesting example is the insect wing, which consists of a membrane and veins. Previously we showed that cracks tend to arrest at the veins, which confer an increased toughness compared to that of the membrane. The Theory of Critical Distances (TCD) is an approach used to predict crack propagation based on the concept of a material-dependant length scale. In the present work, we monitored cracks propagating through wing samples and used finite element analysis (FEA) to model the interaction between cracks and veins. We found that the TCD could accurately predict the passage of a crack through a vein based on an estimate of the average stress over a material-dependant distance ahead of the crack tip. A picture emerges of the wing as a material with toughening mechanisms on two length scales: membrane level (critical distance 0.17 mm) and vein level (critical distance 0.58 mm). This work provides insights into how natural materials achieve enhanced toughness and could have applications as a concept in engineering design.